Electrochemical energy storage by polyaniline nanofibers: high gravity assisted oxidative polymerization vs. rapid mixing chemical oxidative polymerization. Issue 2 (28th November 2014) - Zhao, Yibo; Wei, Huige; Arowo, Moses; Yan, Xingru; Wu, Wei; Chen, Jianfeng; Wang, Yiran; Guo, Zhanhu
Abstract : A rotating packed bed (RPB) rather than stirred tank reactor (STR) produces more uniform polyaniline fibers with better energy storage performance. Abstract : Polyaniline (PANI) nanofibers prepared by high gravity chemical oxidative polymerization in a rotating packed bed (RPB) have demonstrated a much higher specific capacitance of 667.6 F g −1 than 375.9 F g −1 of the nanofibers produced by a stirred tank reactor (STR) at a gravimetric current of 10 A g −1 . Meanwhile, the cycling stability of the electrode is 62.2 and 65.9% for the nanofibers from RPB and STR after 500 cycles, respectively.